Optimized RT-qPCR Detection of Hepatic Lipopolysaccharide-Binding Protein in Diet-Induced Obese Mice - Tjahjono, Yudy; Wedharga, I Gede Putu Adhi; Novita, Bernadette Dian; Tahalele, Paul; Wijaya, Hendy; Soediono, Endang Isbandiati; Hendrata, Adi Pramono; Dewi, Sianty; Wijaya, Sumi; Ervina, Martha; Kuncorojakti, Suryo (Jurnal Medik Veteriner, 2025)
High-throughput RT-qPCR results on hepatic lipopolysaccharide-binding protein (LBP) expression in obese subjects are essential, as they reveal the endotoxin’s role in the development of obesity and non-communicable disease (NCD). This study aimed to optimize RT-qPCR detection of LBP in diet-induced obese mice. This study primarily focused on addressing high variability through reference gene normalization. A total of six male C57BL/6 mice aged 6 weeks were randomly allocated into two dietary treatments (n = 3), consisting of mice fed with the standard chow diet (SCD group) and mice fed with the high-fat and high sucrose diet (HFHS group) ad libitum for 8 weeks. Relative quantification strategies involving the standard 2-ΔΔCt method (calibrator as mean) and the modified 2-ΔΔCt method (calibrator as individual sample-matched biological replicates) were compared in terms of their variability. Obesity was successfully induced in the HFHS treatment group, as indicated by significantly higher body weight, calorie intake, and LBP relative expressions compared to the SCD group. In addition, a sample-specific calibrator approach using the modified 2-ΔΔCt method resulted in lower variability in relative gene expression levels. A modified 2-ΔΔCt method, which utilizes a sample-specific calibrator to counteract sample-specific variability, was successfully employed to address high variability in RT-qPCR results.